PRIMARY SLX TEST USING REAL-TIME PCR BASED ON HIGH RESOLUTION MELTING (HRM) ON MICROFILARIA EXAMINATION - Ihsan, Bagus Muhammad; Sucipto, Cecep Dani; Khayan, Khayan (Faculty of Vocational Studies, Universitas Airlangga, 2021)
Background: Filariasis patients can be a source of transmission if their blood still contains microfilariae. One of the Polymerase Chain Reaction (PCR) methods used is High Resolution Melting (HRM), using primary specificity testing. Purpose: To test the specificity of SLX primer. The samples used for this test were isolates of Salmonella., Klebsiella, Pseudomonas, negative and positive controls for Brugia malayi and Wuchereria bancrofti. Method: The design in this study is a quasi-experiment by testing the specificity of SLX primer using HRMbased real-time PCR based on the Cycle Threshold (CT) value observed through the amplification curve. Result: The real-time PCR results showed that no CT was released in the bacterial samples, and there was a CT value in the positive control. The results of this study indicate that specific SLX primer can be used in identifying microfilariae. Conclusion: SLX primer have a reasonable specificity because they cannot detect the existence of microorganisms in the samples other than microfilariae.